Fast Fashion Product Purchase Decisions : the Impact of Digital Marketing Interaction and Youth's Social Preferences in Semarang City - Dyah Ika KIrana Jalantina; Maria Magdalena Minarsih (Jurnal Multidisiplin Sahombu, 2026)
The rapid growth of the fast fashion industry has encouraged companies to utilize digital marketing strategies to attract young consumers. Current consumer preferences for a fashionable appearance encourage fashion entrepreneurs to quickly adapt to consumer tastes. This study used a descriptive qualitative method with a closed-ended survey. Data were collected using a questionnaire from 40 respondents living in Semarang City aged 18-24 years and actively shopping for fast fashion products. The results show that young consumers have a strong preference for digital purchasing channels, especially social media and e-commerce platforms, to obtain fast fashion products. Young consumers make fast fashion purchases at low to moderate levels within one month. This indicates the existence of behavioral control and value considerations in fast fashion product purchasing decisions. A visual and applied approach is also important in digital marketing strategies, especially in the fashion sector, which relies heavily on aesthetic perception and style relevance.